Qualitative interviews with healthcare staff in four European countries to inform adaptation of an intervention to increase chlamydia testing. Issue 9 (25th September 2017) - McNulty, Cliodna; Ricketts, Ellie J; Fredlund, Hans; Uusküla, Anneli; Town, Katy; Rugman, Claire; Tisler-Sala, Anna; Mani, Alix; Dunais, Brigitte; Folkard, Kate; Allison, Rosalie; Touboul, Pia
Abstract : Objective: To determine the needs of primary healthcare general practice (GP) staff, stakeholders and trainers to inform the adaptation of a locally successful complex intervention (Chlamydia Intervention Randomised Trial (CIRT)) aimed at increasing chlamydia testing within primary healthcare within South West England to three EU countries (Estonia, France and Sweden) and throughout England. Design: Qualitative interviews. Setting: European primary healthcare in England, France, Sweden and Estonia with a range of chlamydia screening provision in 2013. Participants: 45 GP staff, 13 trainers and 18 stakeholders. Interviews: The iterative interview schedule explored participants' personal attitudes, subjective norms and perceived behavioural controls around provision of chlamydia testing, sexual health services and training in general practice. Researchers used a common thematic analysis. Results: Findings were similar across all countries. Most participants agreed that chlamydia testing and sexual health services should be offered in general practice. There was no culture of GP staff routinely offering opportunistic chlamydia testing or sexual health advice, and due to other priorities, participants reported this would be challenging. All participants indicated that the CIRT workshop covering chlamydia testing and sexual health would be useful if practice based, included all practice staff and action planning, and was adequately resourced. Participants suggested minor adaptations to CIRT to suit their country's health services. Conclusions: A common complex intervention can be adapted for use across Europe, despite varied sexual health provision. The intervention (ChlamydiA Testing Training in Europe (CATTE)) should comprise: a staff workshop covering sexual health and chlamydia testing rates and procedures, action planning and patient materials and staff reminders via computer prompts, emails or newsletters, with testing feedback through practice champions. CATTE materials are available at: www.STItraining.eu.